Comparative evaluation of antioxidant, hypoglycemic and hypolipidemic potentials of Black tea from three major tea growing zones of India - Shanta K Adiki; Koushik Bhandari; Prakash Katakam; Gargi Saha; Baishakhi De (International Journal of Pharmacy and Analytical Research, 2022)
Tea is a very popular commercial crop and India is the world’s largest consumer of tea in the world and the second largest producer of tea. Black tea is mostly preferred in Indian context and its multifaceted health benefits are being largely explored. This research article made a comparative study of antioxidant, hypoglycemic and hypolipidemic effect of Assam, Darjeeling and Nilgiri varieties of black tea. Research results have shown that Assam variety of tea has the highest antioxidant, hypoglycemic and hypolipidemic potentials followed by Nilgiri and Darjeeling variety.